Exploring transposons in macroalgae: LTR elements and neighboring genes in red seaweeds - Garcia-Jimenez, Pilar; Robaina, Rafael R. (Frontiers in Marine Science, 2025)
IntroductionThe discovery of transposable elements (TEs), or transposons, by Barbara McClintock in 1950 revolutionized our understanding of genome dynamics. TEs are recognized for their critical role in genetic variability and evolution. They are categorized into two main classes: class I (retrotransposons), which transpose via an RNA intermediate, and class II, which transpose directly via DNA. TEs significantly influence gene expression through insertions that can disrupt gene function. Consequently, organisms have evolved mechanisms to regulate TE activity, particularly under stress conditions, where TE activation can lead to mutations. In marine macroalgae, TEs are known to shape genome architecture, yet little is known about their dynamics.MethodsIn this study, 17 publicly available but non-annotated algal genomes were analyzed to identify and characterize transposable elements. The Earlgrey pipeline, a powerful tool for TE annotation, was used to quantify their diversity and historical activity. A local script was further employed to investigate the genomic co-localization of TEs with annotated protein-coding sequences.ResultsThe analysis revealed significant diversity in TE composition among red, brown, and green algae. Retrotransposons with long terminal repeats (LTRs) were found to be particularly abundant in red algae. Many of these LTRs were located near or within regions encoding proteins, as identified through three protein databases. Notably, these included LTR-specific enzymes such as ribonuclease H, as well as nucleic acid–binding proteins and cation-binding proteins like CCHC-type zinc-finger proteins and haem peroxidase superfamily members, which are involved in stress response pathways.DiscussionThe co-localization of LTRs with stress-responsive protein-coding genes raises intriguing questions about the potential regulatory interplay between TEs and stress adaptation. It remains to be determined whether LTR activity is modulated by the activation of these proteins under stress, or if LTRs have been assimilated into the cellular network to promote protein expression as part of an adaptive response. These findings suggest a promising avenue for exploring the functional integration of TEs into stress resilience mechanisms and highlight their potential role in the evolutionary dynamics of marine algae.